Lonestar Secrets - Coble, Colleen (Nashville, Tenn. : Thomas Nelson, 2008)
Returning to the southwest Texas community of her youth, Shannon Astor runs into a man who once devastated her life and is astonished to see his daughter's uncanny resemblance to Shannon's believed-dead daughter.
Keywords: Texas -- Fiction; Christian fiction; Romantic suspense fiction